A review on notification sending methods to the recipients in different technology-based women safety solutions - A. Z. M. Tahmidul Kabir; Al Mamun Mizan; Plabon kumar Saha; Nirmal Debnath; Tasnuva Tasneem (Institute of Advanced Engineering and Science, 2022)
Women have progressed a lot in terms of social empowerment and economics. They are going for higher education, jobs, and many other similar endeavors, but harassment cases have also been on the rise. So, women’s safety is a big concern nowadays, especially in developing countries. Many previous studies and attempts were made to create a feasible safety solution for women. Out of various features to ensure women’s safety in critical situations, location tracking is a very common and key feature in most previously proposed solutions. This study found mechanisms of sending the location to different types of recipients in various women safety solutions. In addition, the advantages and drawbacks of location sending methods in women's safety solutions were analyzed.